Determinants of drug-related crimes - Recasata, Ken A.; Capuno, Joseph (Quezon City School of Economics, University of the Philippines Diliman, 2020)
Using panel data from the United Nations Office on Drugs and Crime, the study analyzes the determinants of drug-related crimes across various countries and time; given a sample of 81 countries from periods 2005-2006. A panel-data linear regression with juxtaposed fixed-effects and random-effects models are used to account for country-fixed and unobserved effects, respectively, across time and countries; joint endogeneity in independent variables; as well as for measurement errors that may exist in the crime data. The results show that regulatory quality and deterrence have a negative relationship with drug-related crime incidences; and counterintuitively, a positive relationship in corruption controls and carbon emissions. Moreover, causality between drug crimes and violent crimes are not found.
Thesis (BS Economics) - - University of the Philippines Diliman
Includes bibliographical references and appendix.
Keywords: Drug abuse; Drug abuse and crime; Drug control